First report of Cheleocloeon Wuillot & Gillies 1993 (Ephemeroptera: Baetidae) from the Oriental Region - Sivaruban, T.; Srinivasan, Pandiarajan; Barathy, S.; Isack, Rajasekaran; Kluge, Nikita (Zootaxa, 2022)
A new species, Cheleocloeon vaigaiensis sp. n., is described from Southern India based on larvae, imagines and subimagines of both sexes associated by rearing. This new Oriental species is most closely related to the Afrotropical species Cheleocloeon clavifolium Kluge 2016. Formerly, the genus Cheleocloeon Wuillot & Gillies 1993 was known only from Africa, Madagascar and Arabia; this is the first report of this genus from the Oriental Region.